Manajemen Kurikulum Muatan Lokal Keagamaan Dalam Meningkatkan Pendidikan Dakwah Di SMP Negeri 2 Wonosalam Jombang - Moh Ismail; Mar'atul Azizah (Islamic Education Management Study Program of STIT al Urwatul Wutsqo Jombang, East Java, Indonesia, 2023)
The purpose of this study was to find out: 1. How is the implementation of da'wah education at SMPN 2 Wonosalam Jombang? 2. How is the local content curriculum management plan at SMPN 2 Wonosalam Jombang? 3. How is the evaluation of local content curriculum management at SMPN 2 Wonosalam Jombang? The method used in this study is a qualitative approach with a case study type located at SMP Negeri 2 Wonosalam, Jombang. Collecting data using interview techniques, observation, and documentation The data obtained were then analyzed using interactive model data analysis from Miles and Huberman. Based on data analysis, it was found that: 1) Planning for the implementation of local content curriculum activities involves compiling learning tools and matters related to learning; those involved in planning activities are teacher working groups, the head of madrasah, the deputy head of curriculum, the madrasah committee, and pesantren leaders; activities are conducted at the beginning of each semester. 2) In the implementation of local content curriculum management, there are still obstacles, but these obstacles have been overcome in the right way. In the implementation, teachers and students are involved, the choice of implementation of the local content curriculum is adjusted to local regulations, and the needs of the community around the institution and its management are very good. 3) Evaluation of the management of the Javanese local content curriculum using various methods carried out by teaching teachers, generally carried out twice in one semester. For learning the Qur'an, evaluation is carried out by several people according to their level, and activities are carried out after each lesson, at the end of the semester, and at the end of the year.